TINDAK TUTUR ILOKUSI DALAM KUMPULAN CERPEN PILIHAN RIAU POS 2013 MELABUH KESUMAT - Susantiyah, Susantiyah; Auzar, Auzar; Hermandra, Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study titled is Ilocutionary Speech Acts in A Collection of Selected Short Stories Riau Pos 2013 Melabuh Kesumat. This study will describe the form and function of ilocutionary speech acts in a collection of selected short stories by Riau Pos 2013. The research is a qualitative research with descriptive methods. The data in this study are all dialogues between executivies with ilocutionary language forms and their functions. The data is obtained using documentary techniques and notes. Then the data is analyzed by identification and classification based on the form and function of ilocutionary speech acts on the dialogue between the characters in the short story.from the data collected in the collection of short stories, it was found that 58 form of ilocutionary speech acts were classified into five form, inculding assertive, judicial, commissive, expressive, declarative speech acts and 41 speech data that were functions of ilocutionary speech acts, sociable, competitive, and collaborative.Key Words: Ilocution Speech Acts, Short Stories, Riau Pos, Melabuh Kesumat